High School Students’ Perception and Development of Soft skills - Rahate Ellah, Hicham; Azmi, Noureddine (International Journal of Language and Literary Studies, 2023)
Abstract Developing soft skills has become as necessary as hard skills for 21st century EFL learners. Thus, the integration of soft skills teaching and learning in the EFL classroom in the Moroccan high schools is very important. It is claimed that graduates and students lack the necessary soft skills due to the ineffectiveness of the contemporary educational systems that somehow fail to equip students with the necessary soft skills. These systems focus more on equipping students with hard skills. It is said that the lack of soft skills is evident and it results in a big skill mismatch between what students and graduates have and what employers need. Thus, the main objectives of this study are to investigate the extent to which high school students are aware of the importance of soft skills and to explore their favorite methods and school subjects for soft skills development. It also attempts to test the 2nd year baccalaureate students’ development of soft skills. This study used a quantitative methodology to collect numerical data and answer the main questions. The study employed a questionnaire as a tool to gather data. The participants are one hundred students from five high schools in the region of Marrakech-Safi. The results revealed that the majority of high school students aren’t aware of the importance of soft skills. Besides, the majority of students preferred learning soft skills in the language school subjects through education technology. Another important finding is that students’ performance in soft skills is not satisfactory.